Multimedia support for improving preoperative patient education: a randomized controlled trial using the example of radical prostatectomy - Huber, Johannes; Ihrig, Andreas; Yass, Mohammed; Bruckner, Thomas; Konyango-Fellhauer, Beryl Awuor; Lozankovski, Novica; Stredele, Regina Johanna Franziska; Moll, Peter; Schneider, Meike; Pahernik, Sascha; Hohenfellner, Markus (Annals of surgical oncology, 2013)
BackgroundGrowing evidence supports the use of multimedia presentations for informing patients. Therefore, we supported preoperative education by adding a multimedia tool and examined the effects in a randomized controlled trial.MethodsWe randomized German-speaking patients scheduled for radical prostatectomy at our center to receive either a multimedia-supported (MME) or a standard education (SE). Outcomes were measured in a structured interview. Primary outcome was patient satisfaction. In addition, we applied validated instruments to determine anxiety and measures of decision-making. Results were given by mean and standard deviation. For comparison of groups we used t test and chi-square test. For an explorative analysis we applied multivariate logistic regression.ResultsWe randomized 203 patients to receive MME (n = 102) or SE (n = 101). Complete satisfaction with preoperative education was more frequent in the MME group (69 vs 52 %, p = .016) and patients after MME reported more questions (5.7 vs 4.2, p = .018). There was no difference concerning the duration of talks and the number of recalled risks. However, perceived knowledge was higher after MME (1.3 vs 1.6, p = .037). Anxiety and measures of decision-making were comparable. Patients judged the multimedia tool very positive, and 74 % of the MME group thought that their preoperative education had been superior to SE.ConclusionsMultimedia support should be considered worthwhile for improving the informed consent process before surgery (www.germanctr.de; DRKS00000096).
Online: 01 August 2012
Gesehen am 08.11.2018